A structural-historical investigation of  in Jeremiah 6:1-81 - Snyman, S. D. (HTS teologiese studies, 2002)
The text internal features of Jeremiah 6:1-8 are examined, focussing on the demarcation of the pericope, text critical matters and the structural characteristics of the text. A three part division of the pericope is proposed, namely verses 1-3, 4-5 and 6-8. A “Steigerung” between the different parts of the text is detected: in verses 1-3 the people are warned by the prophet to flee from Jerusalem, then in versus 4-5 the shouts of the enemy forces can be heared and finally in verses 6-8 there is a word of warning from Yahweh Himself. Text external features are also investigated. The Gattung can be indentified as an announcement of judgment presented as a warning. Reference is made to two of the well known salvation traditions in Israel: the tradition of the conquest of the land and the Zion tradition.